Modified Non-Gluten Tape Muffin Made With Mocaf And Breadfruit Flour - Ghina Nabilah; Woro Priatini; Ilmiati Tsaniah (Universitas Pendidikan Indonesia, 2022)
A muffin is a sweet cake that is typically served in a cup-shaped dish. Wheat flour is typically used as the primary component in muffins and the majority of market-sold cakes. In this research, the authors will make muffins entirely without using wheat flour but breadfruit and mocaf flour, topping them with cassava tape. It aims to increase the use of regional culinary products, such as the Purwakarta Regency's famous cassava tape, decrease the usage of imported wheat flour, and serve as a source of non-gluten for consumers who must limit or even prevent consuming gluten. This study's methodology uses a descriptive quantitative technique with an experimental approach. Experimental research conducted is a kitchen project to find the effect on certain treatments. Three recipe formulations for the non-gluten sample muffin tape will be tested for organoleptic quality using Analysis of Variance (ANOVA) and descriptive analysis. The MTNG2 sample was the best sample with the highest level of preference, according to the organoleptic test results. Next, 100 consumers from the MTNG2 sample participated in a consumer acceptance test. The consumer acceptability test results receive a score of 4.695, ranking them in the very acceptable category.